Genetic influence on ageing-related changes in resting-state brain functional networks in healthy adults: A systematic review. (June 2020) - Foo, Heidi; Mather, Karen A.; Jiang, Jiyang; Thalamuthu, Anbupalam; Wen, Wei; Sachdev, Perminder S.
Highlights: Low-to-moderate heritability for resting-state functional connectivity (RSFC). APOE ε4 allele associated with alterations in the default mode network. Only one genome-wide association RSFC study to date that identified several SNPs. DNA methylation of the serotonin transporter gene linked to altered RSFC patterns. Abstract: This systematic review examines the genetic and epigenetic factors associated with resting-state functional connectivity (RSFC) in healthy human adult brains across the lifespan, with a focus on genes associated with Alzheimer's disease (AD). There were 58 studies included. The key findings are: (i) genetic factors have a low to moderate contribution; (ii) the apolipoprotein E ε2/3/4 polymorphism was the most studied genetic variant, with the APOE-ε4 allele most consistently associated with deficits of the default mode network, but there were insufficient studies to determine the relationships with other AD candidate risk genes; (iii) a single genome-wide association study identified several variants related to RSFC; (iv) two epigenetic independent studies showed a positive relationship between blood DNA methylation of the SLC6A4 promoter and RSFC measures. Thus, there is emerging evidence that genetic and epigenetic variation influence the brain's functional organisation and connectivity over the adult lifespan. However, more studies are required to elucidate the roles genetic and epigenetic factors play in RSFC measures across the adult lifespan.